1984
DOI: 10.1002/clc.4960071103
|View full text |Cite
|
Sign up to set email alerts
|

Global left ventricular function and regional wall motion in pure mitral stenosis‐Left ventricular function in pure mitral stenosis

Abstract: Summary:Global left ventricular function (LVF) and segmental wall motion of the left ventricle are registered in 113 patients presenting a pure mitral stenosis (MS) and in a control group of 50 individuals. The segmental wall motion is measured on the end-diastolic-end-systolic frames of the left ventricle, obtained from right anterior oblique (RAO) monoplane cineangiography . Measurement of the segmental wall shortening is performed using the Stanford method. Group 1 includes 68 patients (60% of the total num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…The probable causes can be listed as: chronically restricted LV filling due to the structural abnormalities in the mitral valve, increased afterload, myocardial involvement during rheumatic fever, extension of the scar process from the mitral valve into the adjacent posterior basal myocardium, restriction or tethering of the posterobasal myocardium by the scarred mitral apparatus, abnormal interventricular septal motion associated with the right-ventricular overload, and the decrease in LV compliance [2,4]. Conventional ECHO methods such as M-mode and 2D ECHO can detect one fourth of the LV dysfunction in MS [2][3][4][5][6]. In recent years, the studies using TDI [3][4][5] and strain/strain rate imaging [6,7] demonstrated the presence of subclinical LV systolic dysfunction, which was not detected with the conventional ECHO methods in pure MS patients with preserved EF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The probable causes can be listed as: chronically restricted LV filling due to the structural abnormalities in the mitral valve, increased afterload, myocardial involvement during rheumatic fever, extension of the scar process from the mitral valve into the adjacent posterior basal myocardium, restriction or tethering of the posterobasal myocardium by the scarred mitral apparatus, abnormal interventricular septal motion associated with the right-ventricular overload, and the decrease in LV compliance [2,4]. Conventional ECHO methods such as M-mode and 2D ECHO can detect one fourth of the LV dysfunction in MS [2][3][4][5][6]. In recent years, the studies using TDI [3][4][5] and strain/strain rate imaging [6,7] demonstrated the presence of subclinical LV systolic dysfunction, which was not detected with the conventional ECHO methods in pure MS patients with preserved EF.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of impaired left ventricular (LV) systolic function, determined by M-mode and/or two--dimensional (2D) echocardiography (ECHO), is noted in 25-30% of the patients with MS [2][3][4][5][6]. Recently, in the studies using tissue Doppler imaging (TDI) [7][8][9] and strain/strain rate imaging [10,11], which are more sensitive methods compared to the conventional ECHO, the occurrence of subclinical Mehmet Erturk et al, Severity of mitral stenosis and left ventricular function LV systolic dysfunction was confirmed even in MS patients with preserved ejection fraction (EF).…”
Section: Introductionmentioning
confidence: 99%
“…The tethering of posterobasal myocardium or restriction caused by scarred mitral apparatus has been implicated in segmental dysfunction of LV (35). In a recent study performed by Özdemir et al (36) global and segmental LV dysfunction in MS patients was shown by using S and SRs imaging.…”
Section: Discussionmentioning
confidence: 99%
“…As a result they specified that the main pathological mechanism responsible for LV function disturbance was myocardial involvement due to rheumatic process in rheumatic pure MS [30]. Colle et al [31] revealed that rheumatic MS patients had anterior and posterior hypokinesia and mean shortening of hypokinetic segments was lower in MS patients than in normal individuals. They also showed that patients who had contractile abnormality had lower EF and circumferential myofibril shortening velocity.…”
Section: Saadet Guven Et Al Evaluation Of LV Systolic Function Withmentioning
confidence: 99%